Identität und Musikanalyse : Grundlegende Überlegungen zu den Begriffen Habitus und Gestus im Rahmen der Popularmusikforschung - Jost, Christopher; Justus Liebig University Giessen (My University, 2011)
Popular music exists within an excess of different genres and styles. Throughout the decades the practicing of sound ideals has led to a common sense for musicaldistinctions. Both, performers and listeners, are aware that every musical action or creation connects with preexisting pop cultural meanings. But it is also apparent that the musicians themselves enable experience and produce meaning. They address the listener in a multitude of expressive actions that merge into an artistic personal identity. As a consequence of this music analysis has to mediate between cultural formations and the artists´ identities that are conveyed via musical actions and acts of embodiment. Therefore, two theoretical concepts, habitus and gestus, are subjected to fundamental methodological considerations.
Keywords: ddc:780